Cover Picture: Hydrogenation of Carbon Dioxide to Methanol Catalyzed by Iron, Cobalt, and Manganese Cyclopentadienone Complexes: Mechanistic Insights and Computational Design (Chem. Eur. J. 37/2017). Issue 37 (15th May 2017) - Ge, Hongyu; Chen, Xiangyang; Yang, Xinzheng
Abstract : Hydrogenation of CO2 to methanol is one of the most attractive ways for carbon dioxide recycle and hydrogen storage. Our computationally designed Fe, Co, and Mn cyclopentadienone complexes are promising low‐cost catalysts for hydrogenation of CO2 to methanol. Density functional theory calculations also reveal a methanol‐ or water‐mediated proton‐transfer mechanism for H2 cleavage and a direct C−O bond‐breaking process for the formation of formaldehyde as key steps in the catalytic reaction. More information can be found in the Full Paper by X. Yang et al. onpage 8850 .